Al-Qur'an Perspective on the Concept of Islamicpreneurship in Economic Growth - zahro, Fatimatuz; Fakhri, Jamal (JASSP, 2023)
Islamicpreneurship has been inherent in the Prophet Muhammad SAW. This has a very big influence on human activities, especially Muslims. Therefore, Muslims must master the practice of Islamic entrepreneurship that has been taught by the Prophet Muhammad SAW. Islamicpreneurship is an entrepreneurial science with a form of activity to lead, establish, take risks, manage, and become a business owner according to Islamic teachings. This research is qualitative library research, which aims to collect data and information contained in literature, such as books, manuscripts, journals, previous research, and documents. The methods and techniques of data collection in this study are to collect literature related to the research and analyzed the theory used. In this case, the author seeks to describe and analyze the al-Qur'an Perspective on the Concept of Islamicpreneurship in Economic Growth. The application of this concept has also been carried out since ancient times at the time of the prophet, as an example of the noblest Apostle, Muhammad SAW by implementing Islamic entrepreneurship based on the nature of Siddiq, Amanah, tabligh, and fathonah. The practice of Islamicpreneurship is inseparable from the values of Islamic rules intending to worship only to get the pleasure of Allah SWT. Islamicpreneurship provides direction for business practices that must pay attention to norms, ethics, and all forms of Islamic religious values by holding fast to faith, being able to innovate and create, and aiming to provide benefits. In other words, the concept of Islamicpreneurship will significantly affect economic growth.